Integrating SQ4R Technique with Graphic Postorganizers in the Science Learning of Earth and Space (Jurnal Pendidikan IPA Indonesia, 2018)
This study examined the effect of integrating SQ4R reading technique with graphic post organizers on the students’ Earth and Space Science learning achievement and development of metacognitive knowledge. The pretest-posttest non-equivalent control group design was employed in this quasi-experimental method. The sample which consists of 103 seventh grade of secondary school students of SMPN 1 Pontianak was drawn by using intact group random sampling technique. An achievement test and a questionnaire of  Reading-Self Awareness were administered. The findings assert that there are significant difference of students’ achievement (F=5.594, p ‹ 0.05) and development of metacognitive knowledge (F= 13.906, p ‹ 0.05) among groups after having received the three distinctive treatments. Integrating SQ4R reading technique with graphic post organizers reveals an effective impact on the academic achievement (ES= 0.69) and the metacognitive knowledge in reading text (ES = 0.48). It confirms that a science teacher has to execute and model metacognitive strategies intentionally.